SIMBOL SIMBOL BUDAYA DALAM KERIS NAGA KAMARDIKAN KARYA MPU PATHOR RAHMAN - Anggraini, Riska Ajeng; Fianto, Achmad Yanu Alif; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2014)
Indonesia is one country that has a lot of cultural diversity include Anthropology , Sociology and Art . All the cultural diversity ancestors inherited from generation to generation to the next generation . One of the works of art and culture that still exist and persist until today is the work of craft art in the form of a dagger , where the artwork has a meaning and philosophy terms of the form to its usefulness . With the development of times , this dagger turns into a work of art that has a lot of meaning in the philosophy of disclosure , the translation of symbols and expectations , in other words, a keris is a manifestation of the prayer and hope of sipencipta and sipemakainya . Kris kris is often called